Analysis of SAT-1, -2, -3 FMD outbreaks in Africa in 2017–2019 - M. V. Sidorovskaya; S. N. Fomina; S. R. Kremenchugskaya (Ветеринария сегодня)
Data on FMD spread in Africa in 2017–2019 provided by the World Animal Health Organization (OIE) and World Reference Laboratory for Foot-and-Mouth Disease (WRLFMD) were analyzed with the emphasis on the current epidemic situation in Northern Africa, and the analysis results are demonstrated as well. Brief historical information on SAT-1, -2, -3 FMDV recovery in Africa is presented. Diagnostic test results demonstrate that the abovementioned virus serotypes are circulating in the Southern, East and West African countries. However, there are reports on detection of SAT-1 FMDV in the Near East (1961–1965 and 1970) and SAT-2 FMDV in Saudi Arabia (2000), Lebanon (2003), Bahrain, Egypt and Lebanon (2012). Infection of cattle with SAT-1, -2, -3 FMDV in Southern and East Africa is associated with the contacts between the domestic livestock and wild cloven-hoofed ungulates, specifically with African buffaloes (Syncerus caffer). FMDV persists in buffaloes for up to 4–5 years and in buffalo herds living within the limited area of the national reserves – for up to 24 years. Buffaloes are considered to be natural reservoir of the virus. The basic disease control measure in Africa is prevention of any contacts between FMD susceptible livestock and buffaloes in the national reserves and game sanctuaries. Moreover, crucial component of FMD prevention is vaccination of bovines kept in buffer zones around the wild cloven-hoofed ungulates’ habitats against the virus serotypes spread by the latter. Foot-and-mouth disease remains one of the most economically significant infections in the world and it involves losses due to the decrease of the agricultural production as well as due to the international trade restrictions.